CEO Compensation and Earnings Management - Qin, Ziqi (2016)
Over the recent 30 years, the increasing equity-based CEO compensation has attracted a lot of attention of the public. It is recognized as a superb way to mitigate the agency problem by linking firm performance to the compensation package. Therefore, executives may mask the firm performance by manipulating earnings. However, this method may have negative impacts. Improper method to manage earnings may result in accounting scandals. In the first decade of the 21st century, numerous accounting scandals have been disclosed. Motivated by more accounting scandals that have been disclosed and the increasing proportion of equity compensation in the total CEO compensation package, this paper tends to assess the relationship between equity compensation and active level of the manipulation of earnings. The sample consists of 158 companies through seven years. This paper assesses the relationship by testing two models. The first model proves that CEOs with more equity compensation have stronger incentives to manipulate earnings, which is consistent with previous related research. The second model could not prove that CEOs may decrease earnings prior to the option exercise date when they have many options to receive.